Dampak Kebijakan Stimulus Perekonomian Nasional Pada Pembiayaan BPRS di Masa Pandemi Covid-19 - Evi Ekawati; Dinda Fali Rifan; Nur Wahyu Ningsih (Jurnal Akuntansi dan Pajak, 2023)
The COVID-19 pandemic has had impacts and challenges for the business, including the banking financial services industry. Economic activity tends to decline so that the Financial Services Authority (OJK) issues further policies by relaxing regulations in the banking sector to provide more space for liquidity and banking capital so that financial sector stability is maintained amidst the weak economy as a result of the COVID-19 pandemic. This study aims to analyze the impact of the implementation of the national economic stimulus policy on the performance of murabahah financing of Islamic financial institutions during the Covid-19 pandemic. This study uses a qualitative approach with data collection techniques through interviews and documentation. The results of the study indicate that BPRS X, BPRS Y, and BPRS Z in Lampung Province have been able to implement POJK No. 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread of Covid-19. However, only BPRS Z has not submitted periodic reports on the BPRS website on the implementation of POJK No. 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread of Covid-19. This can be interpreted that the BPRS is able to implement several indicators of the National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread of Covid-19.